Last Glacial Maximum in an Andean cloud forest environment (Eastern Cordillera, Bolivia): Comment and Reply - Baker, Paul A.; Bush, Mark; Fritz, Sherilyn; Rigsby, Catherine A.; Seltzer, Geoffrey; Silman, Miles (My University, 2003)
Whether the climate of tropical South America during the Last Glacial Maximum (LGM) was colder and drier or colder and wetter than present day has been widely debated. It is accepted, however, that the LGM in tropical South America was 2–9 °C colder than today (e.g., Betts and Ridgway, 1992; Bush et al., 2001). Without debating the merits of the following choices, if we assume a lapse rate in the LGM similar to the modern one of ~0.6 °C·100 m−1, then an intermediate cooling of 5 °C would lower the boundary between montane cloud forest and the overlying puna grasslands by ~800 or 900 m. Palynologists on both sides of the wet/dry debate have come to similar conclusions about forest-boundary lowering due to temperature decrease (reviewed by Flenley, 1998). In the Eastern Cordillera of Bolivia the modern puna–cloud forest boundary lies ~3400 m above sea level (masl). Ignoring any other environmental changes, LGM cooling would have lowered this boundary to 2500 or 2600 masl.